Analisis Sistem Informasi Manajemen Rumah Sakit Bagian Farmasi dengan Metode HOT-FIT di Rumah Sakit Fitri Candra Wonogiri - Fatimah Mustikawati; Triana, Triana; Khabib Alia Akhmad (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the performance of the Hospital Management Information System SIMRS in the pharmacy unit of RSU Fitri Candra Wonogiri using the HOTFIT model approach. The HOT-FIT model is an evaluation framework that includes four main aspects, namely Human (system users), Organization (organizational support and policies), Technology (system and information quality), and Net Benefit (benefits obtained from system use). This study uses a quantitative method with Structural Equation Modeling data analysis techniques based on Partial Least Square (SEM-PLS), which allows for simultaneous analysis of relationships between variables. Data were obtained from 61 respondents who are SIMRS users in the pharmacy department, through the distribution of Likert-based questionnaires. The results of the analysis show that the four independent variables Human, Organization, Technology, and Net Benefit have a positive and significant effect on SIMRS performance. The Adjusted R-Square value of 0.902 indicates that the model is able to explain 90.2 of the variability in system performance. Empirical findings in the field indicate that the implementation of SIMRS has had a tangible impact on improving work efficiency, accelerating the pharmaceutical service process, and supporting decision-making based on accurate and up-to-date data. Furthermore, active user involvement, managerial support, and the quality of the information technology system are crucial factors in supporting the system's successful implementation. This study confirms that the success of SIMRS depends not only on its technological sophistication but also on strong integration between human and organizational aspects and the resulting benefits. Therefore, a holistic approach to information system evaluation and development is crucial for improving the quality of healthcare services in hospitals.